From audiovisual translation to cultural access - Martins, Cláudia (2020)
Until the end of the 20th century Audiovisual Translation (AVT) sought to fight against the yoke of Translation Studies, which enveloped it in what Díaz Cintas called “the Cinderella mantle” that prevented AVT to stand autonomous. Nonetheless, Gottlieb (1991) regarded the 1990s as the golden age of AVT and thus, in 2008, Díaz Cintas acknowledged that such mantle had “(partially) evaporated”. Can we nowadays consider AVT as a “full-blown research field in its own right” as Bączkowska (2015) upholds, along with other authors? Starting from this premise, I aim at discussing the extent of evolution within AVT which, on the outset, mainly covered subtitling and dubbing to then encompass new modes mushrooming at a fast pace, such as audiodescription or subtitling for the deaf and hard-of-hearing, to name just a few. Therefore, numerous scholars have opted for the phrase ‘media accessibility’ so as to emphasise the particularities of these developing modes that focus primarily on making cultural venues accessible to people with sensory impairments, which move further from a more traditional definition of translation. These venues include not only TV and cinema, but also the performing arts (i.e. theatre, opera or dance) or museums and galleries. Drawing on examples of good practices that have been adopted in Portugal, I intend to reflect upon the role AVT has played in enhancing cultural access.